Characterization of patients with sacrococcygeal pilonidal disease in the Coloproctology Service. Period 2020-2022 - Yasser Muñiz Morales; José Alberto Puerto Lorenzo; Eslinda Cabanes Rojas; Dianelys Molina Macias; Jorge Ernesto González García (Medisur)
Foundation: pilonidal disease is a common condition to suspect in any suppuration of the intergluteal fold that involves the hair follicles of the presacral region. Therefore, its study and analysis is of interest. Objective: to characterize patients with sacrococcygeal pilonidal disease treated in the Coloproctology Service. Methods: Case series study, which included patients, treated with sacrococcygeal pilonidal disease diagnosis, in the Coloproctology Service at the Dr. Gustavo Aldereguía Lima General University Hospital, Cienfuegos, from January/2020 to December/2022. The analyzed variables were: age, sex, comorbidities, anesthetic technique used, surgical strategy used, degree of postoperative satisfaction and postoperative complications. Results: sacrococcygeal pilonidal disease occurs more frequently in males, between the second and third decade of life in healthy patients. Prevail the surgical treatment. Local anesthesia and resective techniques were the most used. Patients with poor postoperative satisfaction predominated. Surgical wound infection and the appearance of seromas were the most representative postoperative complications. Conclusions: sacrococcygeal pilonidal disease occurs mainly in young, healthy patients. Postoperative dissatisfaction predominated in the series, which could be a reason for reflection for future research.